(untitled) (Religious dialogue and cooperation, 2024)
How can we proactively rehearse a collective sense of humanity, and let go of the focus on our cultural differences as an obstacle? The dissimilarity of people has become a popular reason for social exclusion, regularly leading up to hate speech, dehumanization and destruction. This essay demonstrates how community music programs can create a sense of intercultural community, both between musicians as throughout all participants including teachers, family and the audience. Firstly, the relevance of collective music making is discussed along with the ideas of Richard Sennett on music and mutual respect, and of Alicja Gescinska on feeling at home in music. This creates an interdisciplinary framework of political and philosophical theories, which is expanded by psychological research. To maintain respect between people from different cultural and religious backgrounds is not something that tends to be stimulated in the individualistic belief systems of Western commercialisation and competitive education systems. Where do our children and future generations practice teamwork, intercultural communication and a curiosity for cultures that reach beyond their own belief systems? Arts in general, and music in particular, can and should offer fertile grounds for these learnings through working together, active listening and practices in collective resonation. To illustrate these arguments, examples such as the El Sistema Europe Youth Orchestra (SEYO) and Musicians Without Borders will be discussed to show the serious potential of music in the nurturing of mutual respect in an intercultural society. In order to enable such powerful projects, it is essential that governmental institutions, policymakers and academicians support the sustainability and growth of community music programs, to make them widely accessible in areas which could benefit from proactive, creative practices in intercultural and religious dialogue.